2006
DOI: 10.1111/j.1365-294x.2006.02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for isolation by time in the European eel (Anguilla anguilla L.)

Abstract: Life history traits of highly vagile marine species, such as adult reproductive success and larval dispersal, are strongly determined by oceanographic and climatic forces. Nevertheless, marine organisms may show restricted dispersal in time and space. Patterns of isolation by distance (IBD) have been repeatedly observed in marine species. If spawning time is a function of geographical location, temporal and spatial isolation, can easily be confounded or misinterpreted. In this study, we aimed at discriminating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 59 publications
(124 reference statements)
8
82
2
Order By: Relevance
“…When concentrating only on cohorts with larger sample sizes we also observed a weak (albeit not significant) tendency for increased differences over time, which is in accordance with Maes et al (2006) who observed such a pattern between glass eel samples separated by a few consecutive years. The amount of random genetic change over time at neutral loci (genetic drift) is expected to be inversely proportional to the current effective population size (N e ), which is the rationale for estimating this parameter from molecular data using the so-called temporal method.…”
Section: Genetic Effects Of Translocationssupporting
confidence: 91%
See 1 more Smart Citation
“…When concentrating only on cohorts with larger sample sizes we also observed a weak (albeit not significant) tendency for increased differences over time, which is in accordance with Maes et al (2006) who observed such a pattern between glass eel samples separated by a few consecutive years. The amount of random genetic change over time at neutral loci (genetic drift) is expected to be inversely proportional to the current effective population size (N e ), which is the rationale for estimating this parameter from molecular data using the so-called temporal method.…”
Section: Genetic Effects Of Translocationssupporting
confidence: 91%
“…Hence, we looked for indications of a temporal trend (compare Maes et al, 2006) through testing for a correlation between linearized genetic (F ST /(1ÀF ST )) and temporal distance, measured as the number of years lapsing between cohorts. Thus we treated the cohorts from Italy and the Baltic Sea as if belonging to the same population, which appeared justified considering the lack of any detectable spatial genetic divergence.…”
Section: S Palm Et Almentioning
confidence: 99%
“…Pearson's correlation coefficient r, degrees of freedom (df) and p-values result from Mantel's (1967) Similarly, a microsatellite survey in rice, wheat and barley showed nonrandom distribution and frequencies of genomic and EST-derived microsatellites (La Rota et al, 2005), suggesting that genomic microsatellites have the potential for a larger polymorphism than those derived from coding regions, which are length-constrained by purifying selection. While our study detected no increased differences over time, suggesting that heterogeneity among adult samples was not attributable to an IBT pattern, Maes et al (2006) detected a subtle IBT pattern among glass eels. A marginally significant correlation was observed between samples differing by 2-3 years between microsatellite genetic distance and daily distance (r = 0.184, p = 0.043) but not yearly distance (r = 0.095, p = 0.134) or using allozyme genetic distance (daily distance: r = 0.005, p = 0.450; yearly distance: r = 0.077, p = 0.166).…”
Section: Comparison With Previous Genetic Studiescontrasting
confidence: 87%
“…value of NSE and consequent NBE) could determine the F-statistic values obtained with the 22 genetic markers in this study. In addition, the model was run using F-statistic values obtained from literature including the study of Pujolar et al (2009a) conducted using the same markers but on glass eels, plus the studies of Wirth and Bernatchez (2001), Dannewitz et al (2005) and Maes et al (2006) on glass eels using genomic microsatellites. Simulations were run for 200 generations until convergence to stable F-statistic values.…”
Section: The Genetic-demographic Modelmentioning
confidence: 99%
See 1 more Smart Citation